2010
DOI: 10.1002/mnfr.201000108
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐invasion effects of 6‐shogaol and 6‐gingerol, two active components in ginger, on human hepatocarcinoma cells

Abstract: These results suggest that 6-shogaol and 6-gingerol might both exert anti-invasive activity against hepatoma cells through regulation of MMP-9 and TIMP-1 and that 6-shogaol could further regulate urokinase-type plasminogen activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 35 publications
3
79
1
Order By: Relevance
“…This anti-H. pylori action was further confirmed by Mahady et al (2005) and Nostro et al (2006). Recently, Weng et al (2010) demonstrated that [6]-shogaol and [6]-gingerol exerted anti-invasive activity against human hepatocarcinoma cells.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 62%
“…This anti-H. pylori action was further confirmed by Mahady et al (2005) and Nostro et al (2006). Recently, Weng et al (2010) demonstrated that [6]-shogaol and [6]-gingerol exerted anti-invasive activity against human hepatocarcinoma cells.…”
Section: Zingiber Officinale Roscoe Zingiberaceae (Gengibre)mentioning
confidence: 62%
“…In vitro and in vivo findings have indicated that 6-shogaol exerts anti-inflammatory effects [12,13]. Recently, our laboratory and Weng et al have reported the in vitro anti-invasive effects of 6-shogaol against breast carcinoma and hepatocarcinoma cells respectively [14,15]. Shogaols have also been reported to possess antitumor effects and to date, findings have revealed that they are likely to induce cancer cell death via multiple mechanisms.…”
Section: Introductionmentioning
confidence: 91%
“…The pungent vallinoids of ginger, [6]-gingerol and [6]-paradol, exhibit antiproliferation activity in liver, pancreatic, prostate, gastric, and leukemia cancer cells (Lee et al, 1998;Chen et al, 2007;Shukla and Singh, 2007). Furthermore, [6]-shogaol has also been shown to exhibit anticancer activities against breast cancer through the inhibition of cell invasion reduction of matrix metalloproteinase-9 expression (via blockade of nuclear factor activation) (Ling et al, 2010), anti-proliferation activity (through disruption of microtubule network of non-small lung epithelium cancer) (Choudhury et al, 2010), and antiinvasion on human hepatocellular cell (Weng et al 2010). To our knowledge, there has been no report on the anticancer activity of ginger against CCA.…”
Section: Introductionmentioning
confidence: 99%